Avaliação dos efeitos tóxicos individuais e associados de herbicidas a base de glifosato e imazetapir sobre organismos não-alvo - Costa, Gessyca Gonçalves (2018)
Introduction: The dissemination of transgenic crops resistant to glyphosate led to a considerable increase in the application of formulations based on this herbicide in Brazilian crops. An alternative to control populations of glyphosate tolerant weeds is its application associated with another herbicide, imazethapyr, which belongs to the group of imidazolinones. Considering that less than 0.1% of herbicides applied to crops reach their specific targets, it is known that large quantities of these compounds can be found in different environmental compartments, including water resources. Objective: Thus, the objective of this work was to evaluate the effects induced by the commercial formulations Glifosato Atanor (ATN) and Imazetapir (IMZT) isolated and associated (M1, M2 and M3) on non-target organisms through acute toxicity tests with Cucumis sativus, microcrustacean Artemia salina and the embryo- larval stages of zebrafish, including cytotoxicity analysis. Methods: For this purpose, the test with A. salina (Meyer et al., 1982 and OECD 202, 2004), embryo-larval stage of zebrafish (OECD 236, 2013), cytotoxicity assays (Hoechst 33342, Mitotracker red and acridine orange). Results: For the germination of C. sativus, the ATN and IMZT formulations (EC50> 1000 mg / L) and mixtures of ATN + IMZT were not phytotoxic. For the root growth, the IMZT (EC50 = 0.37 mg / L) was more phytotoxic than the ATN (EC50 = 1.97 mg / L), and the ATN + IMZT mixtures had a growth rate of 37.9; 24.7 and 17.2%, respectively. Only ATN induced significant acute toxicity to A. salina (LC50-48h = 9.62 mg/L) and the mixtures did not induce significant effects on the lethality (<20%) of this microcrustacean. For toxicity testing on zebrafish embryos, ATN and IMZT formulations induced similar lethality, with LC50 of 76.50 mg/L and 71.60 mg/L respectively and ATN still caused malformations such as delayed absorption of the yolk sac, cardiac edema and tail deformities (EC50-72h> 55 mg/L). Both formulations inhibited swim bladder inflation with EC50-120h of 26.94 mg/L (ATN) and 53.87 mg/L (IMZT). Both the individual ATN and IMZT formulations as well as the ATN + IMZT mixtures showed a reduction in the percentage of fluorescence in Hoechst stained cells, suggesting the loss of DNA. ATN and IMZT also reduced the mitochondrial potential of larvae exposed to 5 and 50 mg/L, as well as acridine orange stained cells in head, trunk and tail regions at the lowest concentrations. Mixtures of ATN + IMZT did not induce significant lethal and sublethal effects but altered DNA content and mitochondrial potential in zebrafish cells. Conclusions: Therefore, ATN and IMZT formulations and mixtures of ATN + IMZT (M2 and M3) were phytotoxic for C. sativus root growth. ATN was more toxic than IMZT to A. salina, and only M3 was toxic to this species. Although the ATN and IMZT formulations were embryotoxic to zebrafish, the ATN + IMZT mixtures did not induce acute toxicity. At the cellular level, ATN and IMZT at low concentrations were cytotoxic with effects on the nucleus and mitochondria and still accumulated apoptotic cells in some regions of the body of zebrafish larvae.